IMPROVING DIAGNOSTIC CRITERIA FOR OCCUPATIONAL SHOULDER INJURIES - Сааркоппель, Людмила Мейнхардовна; Щетинина, Анастасия Александровна (Medicine in Kuzbass, 2025)
The aim is to determine clinical features and update diagnostic criteria for occupational shoulder injuries associated with physical functional overexertion.Materials and methods. The examination of miners of bauxite mines by underground mining (the main group) was conducted. Mining foremen, electric locomotive drivers and blasters formed a comparison group, whose severity of labor process corresponded to an acceptable class. The scope of survey included an assessment of the neuroorthopedic status, ultrasound and X-ray diagnostic methods, and also isokinetic dynamometry.Results. The main nosological forms of shoulder lesions in the main group were identified. A moderate positive correlation was determined between clinical data and ultrasound results as a screening method of examination. An objective numerical assessment of deficit in functional state of muscles was carried out using isokinetic dynamometry.Conclusion. The obtained results of study of shoulder pathology’s structure in workers in conditions of severity of labor process have a practical significance for substantiating the adjustment of occupational diseases’ list.
Keywords: severity of labor process; shoulder lesions; rotator cuff compression; long head biceps tendinosis; isokinetic dynamometry